2020
DOI: 10.1371/journal.pone.0225355
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of reproductive season on bobcat space use, movement, and resource selection in the Appalachian Mountains of Virginia

Abstract: Across taxa, sex-specific demands vary temporally in accordance with reproductive investments. In solitary carnivores, females must provision and protect young independently while meeting increased energetic demands. Males seek to monopolize access to females by maintaining large territories and defending them from other males. For many species, it is poorly understood how these demands relate to broad-scale animal movements. To investigate predictions surrounding the reproductive strategies of solitary carniv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…We expected to observe temporal differences in sitelevel colonization and extirpation probabilities either seasonally (winter vs. summer) or over the course of our study (survey season 1 to survey season 6); however, neither season nor survey year was included in any of our most supported models for site-level colonization or extirpation. Prior studies have observed differences in resource selection between seasons (McNitt et al, 2020), so we expected to observe similar differences in site-level colonization and extirpation between seasons. The lack of a temporal response indicates that landcover and anthropogenic factors are the main drivers of bobcat occurrence.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We expected to observe temporal differences in sitelevel colonization and extirpation probabilities either seasonally (winter vs. summer) or over the course of our study (survey season 1 to survey season 6); however, neither season nor survey year was included in any of our most supported models for site-level colonization or extirpation. Prior studies have observed differences in resource selection between seasons (McNitt et al, 2020), so we expected to observe similar differences in site-level colonization and extirpation between seasons. The lack of a temporal response indicates that landcover and anthropogenic factors are the main drivers of bobcat occurrence.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies in the region have showed that young male bobcats have very large home ranges (Mayer et al, 2021), so while a camera may be placed within their home range, the extent of the animal's movements throughout their home range may preclude it from having the opportunity to pass by that camera within the 6‐week survey period. Additionally, males typically have larger home ranges and higher frequency of movements within their home range than females as a result of breeding and kitten‐rearing (Conner & Plowman, 1999; McNitt et al, 2020). These differences may affect the probability of detecting a female, and thus decrease overall detection probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the reproductive demands borne solely by females (gestation, parturition, lactation, parental care) can greatly influence the ecology (McNitt et al 2020) and biology (i.e., cortisol levels; Edwards and Boonstra 2018) of carnivores. The hormonal influence may be substantial for months beyond the reproductive period (Bacci et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Within this extent, we calculated the Euclidean distance from the forest and agriculture cover types for each pixel, resulting in two distance covariates (dForest and dAg). We used this approach because distance‐based habitat selection analyses are more robust to telemetry error than classification‐based approaches, provide information about selection for proximity to features that may not be explicitly used by the animal, and eliminate the need for inference based upon a reference land cover category (Conner et al, 2003 ; McNitt et al, 2020 ). We then retrieved stream polyline features from the 2019 USGS National Hydrography Dataset ( https://www.usgs.gov/national‐hydrography/national‐hydrography‐dataset ) and primary/secondary road polyline features from the U.S. Census Bureau TIGER/Line dataset ( https://www.census.gov/geographies/mapping‐files/time‐series/geo/tiger‐line‐file.2011.html ), clipped both layers to the study area extent, and generated Euclidean distance rasters at 30‐m resolutions.…”
Section: Methodsmentioning
confidence: 99%